Weight loss trajectories and psychobehavioral predictors of outcome of primary and reoperative bariatric surgery: a 2-year longitudinal study - Silva, Ana Isabel Pinto Bastos Leite (2019)
Background: Long-term behavioral and psychological aspects associated with weight outcomes after reoperative bariatric surgery have rarely been investigated.Objectives: This study sought (1) to identify differences in weight loss trajectories during the first 24 months in reoperative bariatric surgery (R group) and primary bariatric surgery (P group) and (2) to investigate pre- and postsurgery psychobehavioral predictors of weight loss and weight regain for both groups.Setting: Hospital center and university, Portugal.Methods: This longitudinal study compared an R group (n = 157) and a P group (n = 216). Patients were assessed at presurgery and at 6, 12, 18, and 24 months postsurgery. Assessment included the Eating Disorder Examination Questionnaire and Repetitive Eating Questionnaire diagnostic interviews and a set of self-report measures assessing eating disorder symptomatology, grazing, depression, anxiety, and impulsive behavior.Results: The P and R groups presented a similar trajectory for the percentage of total weight loss (% TWL) (beta = 1.46, standard error = 1.96; Wald chi(2) = .55, P = .457) and weight regain (beta = 1.66, standard error = 2.72; Wald chi(2) = .24, P = .622). No significant presurgery predictors of weight loss and weight regain were found for the P and R groups. Regarding postsurgery predictors, higher Eating Disorder Examination Questionnaire scores (Wald chi(2)((1)) = 6.88, P = .009) and grazing behavior (Wald chi(2)((1)) = 8.30, P = .004) were associated with less %TWL for both groups. Belonging to the P group emerged as a significant predictor of more weight loss (Wald chi(2)((1)) = 7.25, P = .007). Post surgery anxiety predicted less %TWL in R group (Wald chi(2)((1)) = 3.89, P = .043). Considering weight regain, higher postoperative disordered eating (global Eating Disorder Examination Questionnaire; Wald chi(2)((1)) = 4.66, P = .031) was associated with increased weight regain for the P and R groups.Conclusions: Problematic eating behaviors and psychological distress are significa